Characterization of Borrelia burgdorferi tetratricopeptide repeat (TPR) containing proteins - Prativa, Bhatta (My University, 2026)
Borrelia burgdorferi is the causative agent of Lyme disease, the most common vector-borne illness in the United States, affecting around 476,000 people annually with no human vaccine currently available. Unlike other pathogens, B. burgdorferi lacks classical virulence factors; instead, its pathogenesis depends on the ability to invade, disseminate, and persist in host tissues. Proteins containing tetratricopeptide repeats (TPRs) in B. burgdorferi have been shown to contribute to pathogenesis through motility, immune evasion, persistence, and membrane integrity. TPR motifs are 34 amino acid-long, alpha-helical structural motifs found in a variety of proteins that mediate protein-protein interaction. It is defined by a consensus sequence of small and large hydrophobic residues that forms a scaffold for protein binding. In bacteria, TPR-containing proteins have been shown to play roles in numerous cellular processes, including virulence. B. burgdorferi has 23 proteins annotated as putatively containing TPRs, out of which six have been previously characterized as important in pathogenesis. I hypothesize that the 17-remaining TPR-containing proteins of B. burgdorferi also have roles in pathogenesis. This research focuses on characterizing these putative TPR-containing proteins in B. burgdorferi. I began by confirming that all 17 of these proteins contain TPR motifs through the identification of consensus sequences and examination of predicted protein structures using web-based toolkits. My analysis suggests that each B. burgdorferi protein possesses between one and nine TPR motifs which form characteristic antiparallel α-helical structure that are potential sites for protein binding. The identified TPR motifs include variably conserved consensus residues which may prove useful in future studies to determine the contribution of such residues in protein binding. Moreover, I was successful in purifying one of these B. burgdorferi TPR-containing proteins, BB0133. BB0133 is a hypothetical protein containing 5 TPRs that is predicted to reside in the cytoplasm. Purified BB0133 will be used in future studies for the identification of its binding partners. Finally, I investigated the transcriptional changes of the 17 TPR-containing B. burgdorferi proteins in response to environmental conditions. I found that two of the TPR-containing genes, bbj23 and bbj24, were upregulated under in vitro mammalian-mimicking conditions, suggesting they are potential candidates for further studies into their roles in mammalian infection. Overall, this research has helped to build a foundation in the characterization of B. burgdorferi TPR-containing proteins and in the future determining their roles in pathogenesis.
Keywords: Bacteria; Lyme disease; Protein purification; Pathogenesis